How and why might interprofessional patient- and family-centered rounds improve outcomes among healthcare teams and hospitalized patients? A conceptual framework informed by scoping and narrative literature review methods - Abu-Rish Blakeney, Erin; Baird, Jennifer; Beaird, Genevieve; Khan, Alisa; Parente, Victoria M.; O’Brien, Kevin D.; Zierler, Brenda K.; O’Leary, Kevin J.; Weiner, Bryan J. (Frontiers in Medicine, 2023)
Poor communication within healthcare contributes to inefficiencies, medical errors, conflict, and other adverse outcomes. A promising model to improve outcomes resulting from poor communication in the inpatient hospital setting is Interprofessional Patient- and Family-Centered rounds (IPFCR). IPFCR brings two or more health professions together with hospitalized patients and families as part of a consistent, team-based routine to share information and collaboratively arrive at a daily plan of care. A growing body of literature focuses on implementation and outcomes of IPFCR to improve healthcare quality and team and patient outcomes. Most studies report positive changes following IPFCR implementation. However, conceptual frameworks and theoretical models are lacking in the IPFCR literature and represent a major gap that needs to be addressed to move this field forward. The purpose of this two-part review is to propose a conceptual framework of how IPFCR works. The goal is to articulate a framework that can be tested in subsequent research studies. Published IPFCR literature and relevant theories and frameworks were examined and synthesized to explore how IPFCR works, to situate IPFCR in relation to existing models and frameworks, and to postulate core components and underlying causal mechanisms. A preliminary, context-specific, conceptual framework is proposed illustrating interrelationships between four core components of IPFCR (interprofessional approach, intentional patient and family engagement, rounding structure, shared development of a daily care plan), improvements in communication, and better outcomes.